Bacteria associated with the pinewood nematode Bursaphelenchus xylophilus collected in Portugal - Vicente, Cláudia (2011)
Abstract: In this study, we report on the bacterial community associated with the pinewood nematode Bursaphelenchus xylophilus from symptomatic pine wilted trees, as well as from long-term preserved B. xylophilus laboratory collection specimens, emphasizing the close bacteria-nematode associations that may contribute to pine wilt disease development.